Metabolic factors influencing the efficacy of recombinant human growth hormone therapy in children with short stature - Zhong, Xueyu; Chen, Yang; Liu, Geng; Cui, Zhenhai; Luo, Kuanhong; Wu, Zhixin; Xiao, Kangli; Li, Huiqing (Frontiers in Endocrinology, 2025)
ObjectiveThis study analyzed metabolic indicators and height gain in short-statured children within the first year of recombinant human growth hormone (rhGH) therapy, identifying predictive factors for treatment efficacy.MethodsA retrospective analysis of 72 children with short stature (growth hormone deficiency or idiopathic short stature) receiving rhGH therapy (January 2022 to January 2024) was performed. Data included height, weight, age, skeletal age (SA), and laboratory results (IGF1, fasting glucose, insulin, C-peptide, thyroid function, lipids). Analyses focused on height standard deviation score (HSDS), HSDS for SA, and factors associated with 12-month changes in HSDS for SA (△HSDS for SA).ResultsThe mean initial rhGH dose was 0.053 ± 0.010mg/kg/day, with a mean starting age of 8.36 ± 2.24 years. Significant increases in HSDS and HSDS for SA were observed after 12 months. △HSDS for SA negatively correlated with baseline homeostasis model assessment of insulin resistance (HOMA-IR) and fasting insulin, and positively correlated with baseline free triiodothyronine (FT3). Children with △HSDS for SA>0.5 had lower baseline insulin and HOMA-IR, and higher FT3, high-density lipoprotein cholesterol (HDL), and hemoglobin.ConclusionsInsulin resistance, hyperinsulinemia, FT3, and HDL determine rhGH efficacy in short-statured children. Metabolic profiling optimizes rhGH therapy, and targeting insulin resistance may improve growth outcomes.